B‐DNA Structure and Stability as Function of Nucleic Acid Composition: Dispersion‐Corrected DFT Study of Dinucleoside Monophosphate Single and Double Strands. Issue 5 (16th August 2013) - Barone, Giampaolo; Fonseca Guerra, Célia; Bickelhaupt, F. Matthias
Abstract We have computationally investigated the structure and stability of all 16 combinations of two out of the four natural DNA bases A, T, G and C in a di‐2′‐deoxyribonucleoside‐monophosphate model DNA strand as well as in 10 double‐strand model complexes thereof, using dispersion‐corrected density functional theory (DFT‐D). Optimized geometries with B‐DNA conformation were obtained through the inclusion of implicit water solvent and, in the DNA models, of sodium counterions, to neutralize the negative charge of the phosphate groups. The results obtained allowed us to compare the relative stability of isomeric single and double strands. Moreover, the energy of the Watson–Crick pairing of complementary single strands to form double‐helical structures was calculated. The latter furnished the following increasing stability trend of the double‐helix formation energy: d(TpA)2 <d(CpA)2 <d(ApT)2 <d(ApA)2 <d(GpT)2 <d(GpA)2 <d(ApG)2 <d(CpG)2 <d(GpG)2 <d(GpC)2, where the energy differences between the last four dimers, d(ApG)2, d(CpG)2, d(GpG)2 and d(GpC)2, is within 4.0 kcal mol−1, and the energy between the most and the least stable isomers is 13.4 kcal mol−1. This trend shows that the formation energy essentially increases with the number of hydrogen bonds per base pair, that is two between A and T and three between G and C. Superimposed on this main trend are more subtle effects that depend on the order in which bases occur within a strand from the 5'‐ to the 3'‐end.